2020
DOI: 10.1080/13683500.2020.1835841
|View full text |Cite
|
Sign up to set email alerts
|

Business environment effect on business visitor arrivals to New Zealand

Abstract: This research investigates the impact that New Zealand's business environment has on its international business visitor arrivals. Within a gravity modelling framework, data for twenty-four main visitor origin countries are used for empirical analysis for the period 2004-2013. The core contribution of our research is that our empirical results provide strong evidence that the interaction of internet diffusion, commercial bank presence and shipping services with international trade are statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…From another perspective, Kim et al (2018) highlighted regulatory quality and the rule of law as the characteristics of governance with a greater effect on international flows in tourism, and these authors revealed that the effect of improving institutional quality on tourism is stronger in high-income countries than in emerging economies. In addition to the mentioned, Gani and Clemes (2020) confirmed that business infrastructure is associated with foreign business visitors, while the authors emphasized that open trade policies, together with improving the business environment, play an important role in this area. Dragicevic et al (2012) also pointed to investments and improvements in the planning and development of tourism products as a potential source of a competitive business tourism destination.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…From another perspective, Kim et al (2018) highlighted regulatory quality and the rule of law as the characteristics of governance with a greater effect on international flows in tourism, and these authors revealed that the effect of improving institutional quality on tourism is stronger in high-income countries than in emerging economies. In addition to the mentioned, Gani and Clemes (2020) confirmed that business infrastructure is associated with foreign business visitors, while the authors emphasized that open trade policies, together with improving the business environment, play an important role in this area. Dragicevic et al (2012) also pointed to investments and improvements in the planning and development of tourism products as a potential source of a competitive business tourism destination.…”
Section: Discussionmentioning
confidence: 66%
“…Looking at the business environment from a broader perspective, it can be said that the business environment could be recognized as the various phenomena owing to the organization control, which embraces a series of resources and actors that influence the forms, management, and fate of enterprises (Duncan, 1972;Machová and Vochozka, 2019;Vochozka et al, 2020a). Among other business effects, Gani and Clemes (2020) showed that a country's domestic business environment can influence trade in services, such as attracting visitors for business purposes. Their research was based on the hypothesis that countries engaged in easing the process of business formation will attract international investors, resulting in the establishment of more businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigelský et al ( 2021 ) empirically found that institutional innovation has the greatest impact on tourism expenditure by using the data of 36 OECD countries in the WTTC database. Gani and Clemes ( 2021 ) analyzed the tourism data of 24 countries within the framework of the gravity model and concluded that an open trade environment and a good business environment could attract more international business tourists and obtain additional benefits. Kim et al ( 2018 ) verified that the improvement of system quality could obtain higher international tourist income, and the quality of regulation and rule of law has greatly affected the flow of international tourism.…”
Section: Literature Reviewmentioning
confidence: 99%